2018
DOI: 10.1111/aji.12836
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33/ST2 axis affects the polarization and efferocytosis of decidual macrophages in early pregnancy

Abstract: This study indicates that IL-33 secreted by dMφs promotes M2 bias at the feto-maternal interface, and as a result, RSA might attribute to the disturbance of IL-33/ST2 axis and the enhancement of efferocytosis of dMφs subsequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…IL-33, a member of the IL-1 family, induced the proliferation of cytotrophoblasts (CTB) and triggered the migration of EVT by interacting with the IL-33 ligand ST2L (102). Dysregulation of the IL-33/ST2 signaling pathway may skew normal pregnancy-derived dMϕs and U937 cells into the M1 phenotype (103). Meng et al observed that the levels of RANKL/RANK were reduced in villi and decidua from miscarriage patients compared to those from normal pregnancy patients.…”
Section: The Roles Of Macrophages In Pregnancy Complicationsmentioning
confidence: 99%
“…IL-33, a member of the IL-1 family, induced the proliferation of cytotrophoblasts (CTB) and triggered the migration of EVT by interacting with the IL-33 ligand ST2L (102). Dysregulation of the IL-33/ST2 signaling pathway may skew normal pregnancy-derived dMϕs and U937 cells into the M1 phenotype (103). Meng et al observed that the levels of RANKL/RANK were reduced in villi and decidua from miscarriage patients compared to those from normal pregnancy patients.…”
Section: The Roles Of Macrophages In Pregnancy Complicationsmentioning
confidence: 99%
“…During the menstrual cycle, in the endometrium, immature DC-SIGN + cells can transform into mature CD83 + DCs by exposure to antigen or inflammatory cytokines, which suggest that DCs are involved in the uterus defense against pathogens (103). Kammerer et al reported that decidual DC-SIGN + cells in situ and in vitro exhibit similar functions and phenotypes as immature DCs and these cells could mature in cell culture (104, 105).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…However, the majority of decidual macrophages do not fit the M1‐M2 paradigm . Rather, most of the decidual macrophages display a unique, M2‐like phenotype throughout pregnancy . Decidual macrophages from women who underwent spontaneous labor at term or preterm labor, however, exhibit an M1‐like pro‐inflammatory phenotype .…”
Section: Introductionmentioning
confidence: 99%